Etiology, consequences, and solutions of working women's work-life conflict: a qualitative study - Zahra Hosseini; Seyyede Fateme Rahimi; Fatemeh Salmani; Mohammad Reza Miri; Teamur Aghamolaei; Reza Dastjerdi (BMC, 2024)
Abstract Introduction Work-life conflict (WLC) is important in organizational behavior research and human resource management. The present research aimed to investigate the underlying causes, consequences, and solutions to WLC in Iranian working women. Materials and methods The present qualitative study was conducted through a content analysis method among 19 working married women in Birjand, a city in the east of Iran, from December 2021 to February 2022. To collect the data, semi-structured interviews were held. The average interview time was 45 minutes, and all interviews were recorded upon the participants' consent. Finally, after coding, the information was analyzed with MAXQDA software. Findings The causes of conflict included 4 main categories of individual, interpersonal, organizational, and cultural factors, with seven subcategories: the pressure of the mother's role at home, personality traits, lack of individual skills, insufficient support, work characteristics, organizational policies, and the traditional role of women in society. The consequences of conflict included 2 main categories, Decreasing quality of life and work problems with 4 subcategories: physical and mental illnesses, forgetting one's role towards others, limiting social communication, and reducing productivity. Conflict resolution methods included 3 main classes of individual-oriented, other-oriented, and organization-oriented with 8 subclasses: program-oriented, meaning-oriented, emotion-oriented, avoidance, emotional support, instrumental and work support, support work policies, and correct management views. Conclusion To solve the problem of conflict, different aspects should be considered and help to solve this challenge by influencing each dimension.